1999
DOI: 10.1029/1999gl900293
|View full text |Cite
|
Sign up to set email alerts
|

The source region of an interplanetary type II radio burst

Abstract: Abstract.We present the first observation of the source region of an interplanetary type II radio burst, using instruments on the Wind spacecraft. Type II radio emission tracks the motion of a CME-driven interplanetary (IF) shock which encounters the spacecraft. connection times to the shock, we infer the existence and characteristic size of large scale structure on the shock front. The type II radio emission seems to be generated in a small bay upstream of the shock, and this may account for some splitting st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
211
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(230 citation statements)
references
References 13 publications
(15 reference statements)
18
211
0
1
Order By: Relevance
“…Reiner et al (1998a) has suggested that the intermittent nature of type II emissions implies multiple, distinct emission regions. It has also been shown with both remote sensing (Reiner et al 1998a(Reiner et al , 1998b and in situ observations (Bale et al 1999) that the source region of type II emission lies upstream of CME-driven shock fronts. Taken together, these observations suggest that type II emission is generated in multiple foreshock regions upstream of IP shocks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reiner et al (1998a) has suggested that the intermittent nature of type II emissions implies multiple, distinct emission regions. It has also been shown with both remote sensing (Reiner et al 1998a(Reiner et al , 1998b and in situ observations (Bale et al 1999) that the source region of type II emission lies upstream of CME-driven shock fronts. Taken together, these observations suggest that type II emission is generated in multiple foreshock regions upstream of IP shocks.…”
Section: Introductionmentioning
confidence: 99%
“…The in situ terrestrial foreshock has been extensively studied by many spacecraft. In contrast, only one in situ IP foreshock region has been described in the literature (Bale et al 1999). In this section, we will review the basic characteristics of electron acceleration and Langmuir wave generation at the terrestrial foreshock, and outline our analogous measurements upstream of IP shocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ripples in the shock surface [Bale et al, 1999], in which case, parts of the shock magnetically connected to the upstream region need not have the same 0B,• as at the shock crossing. This is also likely due to the shock being curved (even without ripples) or to B varying in space.…”
Section: B• ~ 860 At the Crossing) These Observations Implymentioning
confidence: 99%
“…Of particular interest are observations of radio events that follow solar flares and coronal mass ejections (CMEs). Type II solar radio bursts, for example, are associated with radio emission produced near the local plasma frequency (f p ) and its harmonic (2f p ) upstream of a traveling shock wave, itself often driven ahead of a CME [Wild et al, 1963;Cane et al, 1981Cane et al, , 1987Reiner et al, 1998;Bale et al, 1999;Knock et al, 2001].…”
Section: Introductionmentioning
confidence: 99%